2020
DOI: 10.3311/ppci.15360
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hydric Swelling on the Mechanical Behavior of Egyptian Helwan Limestone

Abstract: This study was concerned at a limestone quarry located southeast of Helwan city, Egypt, in order to investigate the effect of hydric swelling on the geomechanical aspects of limestone rocks. The Volume of Egyptian limestones change due to the presence of clay minerals (swelling/shrinking). These changes in volume induced by changing environmental conditions, high temperature and fluctuation of the relative humidity, causes accelerated physical deterioration of limestone. The rainfall is infrequent, and it is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The limestones used for the construction of the historical stone monuments in Cairo come from local middle and late Eocene outcrops (47.8-33.9 million years ago) located in Mokattam, Helwan and Giza areas (El-Nahhas et al, 1990;Ahmed et al, 2006;Park and Shin, 2009;Aly et al, 2015Aly et al, , 2020. These materials are still being used for stone replacement or rebuilding works in monuments preservation practice as well as for modern buildings.…”
Section: Methodsmentioning
confidence: 99%
“…The limestones used for the construction of the historical stone monuments in Cairo come from local middle and late Eocene outcrops (47.8-33.9 million years ago) located in Mokattam, Helwan and Giza areas (El-Nahhas et al, 1990;Ahmed et al, 2006;Park and Shin, 2009;Aly et al, 2015Aly et al, , 2020. These materials are still being used for stone replacement or rebuilding works in monuments preservation practice as well as for modern buildings.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on schists have observed a slight mass loss (Mottershead [55]) and fracturing and splitting (Wells et al [56]). Swelling and strength decrease have been related to the presence of clay minerals for limestones (Aly et al [57]) and for tuffs (Pötzl et al [58]), a process also reported for other igneous rocks such as kersantite, affecting cracking patterns (Tiennot et al [59]). Also in tuffs, the effects of wetting-drying were ascribed to the interaction between water and pore characteristics and zeolites (Lubelli et al [60]).…”
Section: Wettingmentioning
confidence: 90%
“…Eocene limestones extracted from the local quarries of Mokattam and Helwan areas have been exploited for the construction of monuments in Cairo since past until today (Fitzner et al 2002;Aly et al 2015Aly et al , 2018Aly et al , 2020. Additionally, several of them were reconstructed many times partially or completely over the centuries.…”
Section: Methodsmentioning
confidence: 99%